Impact Of Meteorological Drought On Maize And Sorghum Production In Fedis, Deder And Shinile Woredas, Ethiopia - Tigabu Muche (ASTU, 2018)
In Order To Adapt And/Or Mitigate The Impact Of Md, Md Assessment Has To Form One Dimension Of Research To Be Done; Whereas, The Use Of Md Indices And Different Soft Wares Provides Wide Scope In Drought Risk Detection And Mapping. Consequently, This Study Was Conducted In Eastern Harerghe And Shinile Zones With The Objective Of Assessing Md Risk And Preparing Md Risk Zone Map Using Rainfall (Rf) And Yield Data. To Assess And Examine Spatiotemporal Variation Of Seasonal Md Patterns And Severity, Four Drought Indices Namely, Percent Of Normal (Pon), Water Requirement Satisfaction Index (Wrsi), Standard Precipitation Index (Spi) And Natural Difference Vegetation Index (Ndvi) Anomaly Are Applied. To Characterize Temporal Md, Onset, Cessation, Length Of Growth Period (Lgp) Of Seasons, Its Impact On Maize And Sorghum Yields With Rainfall, The Yield Data Were Utilized. A Late Onset Or Early Termination And Duration Of Sowing Can Initiate Or Exacerbate Drought Conditions. The Result Derived From Indices For The Study Period Cropping Seasons Experienced Enhanced Md With Observed Spatial Difference In Severity Level Over The Study Areas. The Impact Of Md On Crop Production Was Measured Through Yield Reduction. Generally, The Index Results Are With Results Of Yield Reduction Depicting That Yield Reduction Is Largely Attributed To Md. The Result Revealed That Wrsi, Spi And Ndvi Anomaly Express Decreased And The Grain Yield Decreased With The Time Over The Study Areas. Thus, Wrsi Can Be A Good Indicator For Occurrence Of Md. The Result Indicated That The Areas Are Classified Into Slight, Moderate And Severe Md Risk Zone. Thus, The Md Risk Mapping Can Be Useful To Guide Decision Making Process In Drought Monitoring And To Reduce The Risk Of Drought On Agricultural Production.